Association between a large plasmid and 15- to 17-kilodalton antigens in virulent Rhodococcus equi. - Takai, S (1991)
Rhodococcus equi strains showing 15- to 17-kDa antigens in immunoblots were found to be virulent in mice. To study the genes specific to these antigens in virulent R. equi, we compared plasmid profiles, immunoblot profiles, and murine pathogenicity profiles of 10 strains of R. equi. All the strains showing 15- to 17-kDa antigens contained a large plasmid of approximately 85 kbp and were virulent in mice; however, the remaining strains lacked both the antigens and the large plasmid and were avirulent in mice. Mutants of virulent strains ATCC 33701 and L1, which were cured of the large plasmid by repeated passage at 38 degrees C, lacked the 15- to 17-kDa antigens and showed a dramatic decrease in lethality in mice. These results suggested that the presence of an 85-kbp plasmid may be essential for virulence and expression of 15- to 17-kDa antigens of R. equi and offered support for earlier observations that freshly isolated strains of R. equi killed mice, whereas laboratory-adapted strains did not.